A Model of Complete Privatization via auction for the Post Office - de Arruda, Marcelo (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2018)
The purpose of this study was to determine which would be the most adequate model of privatization for the Brazilian Post and Telegraph Corporation (ECT). It mainly considers the factors of the increase of the sector’s operational efficiency, fiscal impact and applicability in the Brazilian context. At first, it was defined the position of the Post Office in the Brazilian postal service market. Then, the privatization principles were brought based on the results of the privatizations that happened in Brazil and in different countries, where positive results were registered. Besides, it is highlighted what it must be avoided from past experiences in order to have a more effective privatization. In the third section of the article, a comparison between the pulverized and consolidated privatization models is made through the review of empirical works, and it was observed that a higher number of positive cases and a greater viability in favor of the concentrated model via auction for the Post Office. In the fourth section, the auction phases are detailed and combined with the need of a sector liberalization policy so that the expected improvements are achieved.